PEMANFAATAN TEKNOLOGI DALAM PENULISAN KARYA TULIS ILMIAH UNTUK MENCEGAH PLAGIASI - Alfiyah Agussalim; Dwi Nur Handayani (Universitas Bina Taruna Gorontalo, 2023)
Technology is something that is needed by humans today, through technology, various human jobs can be completed easily and quickly. Technology has been utilized by various fields. One of them is the field of education, especially higher education which is closely related to writing scientific papers. Therefore, every tertiary institution requires lecturers and students to produce quality scientific papers that are free of plagiarism. One effort to prevent plagiarism in writing scientific papers is through the use of Mendeley's application, which is a form of technology that makes it easier for lecturers and students to do citations and manage references. However, there are still many lecturers and students who are not proficient in using the Mendeley application. For this reason, through this community service activity which is carried out in the form of a webinar using a zoom meeting, it is hoped that it can improve the quality of scientific writing by lecturers and students through the use of the Mendeley application, so as to prevent plagiarism.